Ekonomi Islam; Kepemilikan dan Tauhid dalam Islamic In Transition Muslim Perspecites - Buhari, A Taufiq (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2024)
The theory of private ownership is wealth owned by society, but a person is given conditional freedom of authority, so controlling wealth is a mandate and it is legal to take advantage of it without restrictions according to the Shari'a which must respect the rights of others or not endanger the interests of the general public. A person's rights to their wealth are limited by certain guidelines and receive review from the government with the aim of protecting the wealth of small community groups so that it remains in line with the objectives of Islamic economics in overcoming capital accumulation and centralization of power. Ownership of property according to absolute theory is contrary to Islamic law, because absolute ownership belongs only to Allah SWT. Humans only have ownership rights as a trust, which must be held accountable to the presence of Allah SWT.